2012
DOI: 10.2478/v10181-012-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

The examination of biophysical parameters of skin (transepidermal water loss, skin hydration and pH value) in different body regions of ponies

Abstract: The purpose of this study was to evaluate transepidermal water loss, skin hydration and skin pH in normal ponies. Sixteen ponies of both sexes were examined in the study. Measurements were taken from seven different sites: the neck region, the shoulder, thorax, lumbar, inguinal, lip region and the auricle. In each of the regions transepidermal water loss (TEWL), skin hydration and skin pH were measured. For transepidermal water loss, the lowest values were observed in the lumbar region (9.71g/hm2), while the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 24 publications
(90 reference statements)
5
12
0
1
Order By: Relevance
“…Published research reports on this parameter in horses discussed the effect of sex and body region on TEWL (also skin hydration and skin pH were examined). These studies corroborated the claim that TEWL values differ significantly according to the body region under investigation (Szczepanik et al 2012(Szczepanik et al , 2013 and in "Felin" ponies, a greater variability between the body regions assessed was observed (10 statistically significant differences) than in Polish koniks (6 statistically significant differences, only in one body region). Sex of the animals, however, was not found to influence TEWL values.…”
Section: Discussionsupporting
confidence: 78%
“…Published research reports on this parameter in horses discussed the effect of sex and body region on TEWL (also skin hydration and skin pH were examined). These studies corroborated the claim that TEWL values differ significantly according to the body region under investigation (Szczepanik et al 2012(Szczepanik et al , 2013 and in "Felin" ponies, a greater variability between the body regions assessed was observed (10 statistically significant differences) than in Polish koniks (6 statistically significant differences, only in one body region). Sex of the animals, however, was not found to influence TEWL values.…”
Section: Discussionsupporting
confidence: 78%
“…Gillard et al (2009) reported statistically significant differences between long-and short-haired breeds. When comparing the results obtained in the present study with the results obtained for "Felin" ponies (Szczepanik et al 2012), higher values were observed for the parameter in all regions assessed, which may mean that, similarly to dogs, TEWL values may depend on horse breed as well.…”
Section: Discussionmentioning
confidence: 55%
“…(to measure skin pH, results on the pH scale). The same instrumentation was used in previous studies in dogs, cats and ponies (Young et al 2002, Hester et al 2004, Yoshihara et al 2004, Shimada et al 2009, Hightower et al 2010, Szczepanik et al 2011, Szczepanik et al 2012. For all parameters, the mean, standard deviation and median were calculated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations